CRITICAL THINKING SKILLS OF STUDENTS FROM THE ASPECT OF STRATEGY AND TACTICS IN SOLVING MATHEMATICAL PROBLEMS - Adinda, Anita (International Journal of Insights for Mathematics Teaching (IJOIMT), 2019)
This study aimed to determine students' critical thinking skills from aspects of strategy and tactics in solving mathematical problems. This study used a qualitative approach with descriptive methods. The subjects of this study consisted of 5 graduate students in Malang. The instrument used was a test of critical thinking skills from aspects of strategy and tactics and interviews. The results of the description and interview analysis showed that students' critical thinking skills from the aspect of strategy and tactics in solving critical thinking problems were low. For each indicator of strategy and tactics aspects, critical thinking skills from the aspect of strategy and tactics on indicators revealed high-level problems, critical thinking skills from aspects of strategy and tactics to indicators formulated alternative solutions, used arguments and re-examined relatively low.